Teachers as Victors: Navigating Shifts in Teaching and Learning During the Covid-19 Pandemic - Pillay, Lucas (Studies in Learning and Teaching, 2026)
This article explores how teachers managed shifts in the teaching and learning process during the COVID-19 pandemic and offers insights for designing an intervention program. Conducted as a narrative inquiry, the study involved eleven participants across three secondary and three primary schools in KwaZulu-Natal. Adopting a qualitative, interpretivist approach, data were collected through collages, reflective journals, and interviews. Multiple methods of generating data were selected: collages, reflective journals, and structured interviews. Kurt Lewin’s theory of change was used as a theoretical framework to offer lenses in exploring and understanding how teachers navigate these changes, and it provided a framework for overcoming the challenges in education during crises. During data interpretation and analysis, findings were organized around key themes and sub-themes. The research findings indicate that teachers adapted to the changes brought about by COVID-19 through a range of trial-and-error strategies. The study resulted in the creation of a model and guide for developing context-specific intervention programs. Furthermore, from this study, the researcher developed a theory called ‘Navigating Change Theory.'